Implications of Wet-Rice Farming on Human Health and Physical Environment in Kenya: a Comparative Study in Mwea Irrigation Settlement Scheme, Kenya (Global Journal of Science Frontier Research, 2016)
This paper examines the implication of wet-rice farming or irrigated agriculture on the physical environment and human health. Environmental problems seem to have increased in the recent past posing a major threat to irrigation development. Several environmental problems created by irrigation development in Mwea Irrigation Settlement Scheme (MIS) could be attributed to improper understanding of the complex processes involved in the irrigation system. The main objective of this study was to examine cases and causes of some environmental and health problems and planning related issues in MIS. An environmental planning and management methodology is suggested which will attempt to minimize or at least mitigate against the environmental and health problems.
Keywords: environmental problems; irrigation development; human health problems; comparative method